McDonald's in Indonesia and Its Emerging Political and Security Risks [McDonald di Indonesia dan Risiko-risiko Politik dan Keamanan yang Timbul] - Achmad, Fauzan Sameer; Nasution, Elyzabeth Bonethe (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2023)
McDonald’s was embroiled in controversy following the decision of its branch in Israel to donate the company’s food products to the Israel Defense Forces (IDF), which has been accused of committing genocide on the people of Palestine. The company was boycotted by many worldwide, including the people of Indonesia which had always voiced their strong support for Palestine. The situation highlights a possible threat to McDonald’s as the independence of its individual national branches could result in clashing actions and negative public reception. Moreover, McDonald’s must be wary of the malleable governmental statuses and relationships in the countries it operates in, such as Indonesia, in which it originally opened during an extremely authoritarian regime before the country’s shift into a democratic system. However, the tides have been changing once again as recent political events have put Indonesia’s democracy under the threat of regression. With this newfound situation, McDonald’s must be able to find the proper solutions to address its emerging political and security risks.